As interfaces entre a Saúde Mental e a Justiça: Problematizando as solicitações judiciais em um Centro de Atenção Psicossocial - Lima, Camila da Silva Eidam de (2019)
The federal constitution, promulgated in 1988, ensure health like a right for everyone. This way, it´s common the justice interven on the public services,to assue the access to this right, mainly the mental health care. This search intend to know how is the relation between justice and mental health services in a city of Paraná State with a qualitative characterThe metodology used to production of dados was participant observation in a meeting with justice and mental health workers, semi-sructered interview and data collection in offices received between the years 2017 and 2018 in the CAPS II service. To analizy the data, was used Institucional Analysis concepts, to know how the work process impact on them and how this reflect on the service provided to community. The results show the articulation between mental health services and the justice with the aproximation and a knowledge about the network. Consider then, the importance of the network and intersectoriality as a support for the job. That way, consider the public ministery working for the liberty like the mental health services, with the same proposal of work.